A model of risk and mental state shifts during social interaction - Hula, Andreas; Vilares, Iris; Lohrenz, Terry; Dayan, Peter; Montague, P. Read (PLOS Computational Biology, 2018)
Author summary In multi-round games in which players can benefit by trusting each other, swift and catastrophic breakdowns can arise amidst otherwise efficient cooperation. We present a model that quantifies this as a form of anger, and we exploit novel algorithmic improvements in inference based on the model to examine exchanges involving healthy volunteers and people suffering from personality disorders. This provides a new view on the problems that can underlie social interactions.